(untitled) (Agricultural Engineering, 2016)
The paper presents environmental conditions for the selected location of a landfill site on the area of Stary Sącz designated for deposing neutral waste from the installation for secondary segregation of waste. Based on the productivity of the selected municipal waste parameters of accumulation indicators were detennined strictly correlated with the amount of waste predicted for disposal. Components of the facility were selected including the requirements of the resolution as of 30th April 2013 on landfill sites (Journal of Laws 2013 item 523) for application of solutions for protection of water, soil and atmospheric air environment in its surroundings against the negative impact of waste. The paper also refers to the final stage related to closing of a landfill with the assumed plan of its reclamation. The article was summed up with conclusions indicating the limited possibility of location of such a facility on the selected area on account of its location close to Poprad River and on the area of the Main Reservoir of Underground Water. The objective of the paper was to make an attempt to choose components of the installation for neutralization of waste in Stary Sącz taking into account the local environmental conditions.